1965
DOI: 10.1084/jem.121.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Studies of Lysosomes and Lysosomal Enzymes in Virus-Infected Cell Cultures

Abstract: Chick embryo cells: These were obtained from 10-day-old chicks and grown in a tris0ay-droxymethyl)aminomethane-bffffered Gey's solution with peptone and lactalbumin hydrolysate (4). They were infected after 2 days' growth on coverslips or in 6 mm diameter Petri dishes.HeLa cdls: These were propagated in medium 199 plus 5 per cent inactivated calf serum and were infected 3 to 6 days after subculture by trypsinization. 463

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…(3) It is possible that drug-induced metabolic errors or lysosomal membrane instability during Gj may lead to the subsequent appearance of chromosomal damage during or after DNA systhesis [2,3,25]. To us, this appears to be the most likely explanation.…”
Section: Discussionmentioning
confidence: 97%
“…(3) It is possible that drug-induced metabolic errors or lysosomal membrane instability during Gj may lead to the subsequent appearance of chromosomal damage during or after DNA systhesis [2,3,25]. To us, this appears to be the most likely explanation.…”
Section: Discussionmentioning
confidence: 97%
“…of RA (3, 5, 6, 12) is sharpened by the fact that two persistent characteristics of rheumatoid synovium in vitro (accelerated synthesis of hyaluronate and increased cellular acid phosphatase content) can be induced experimentally in specific cell systems by exogenous virus infection (19,20). Although at present there is no direct evidence that a virus is basic to the pathogenesis of rheumatoid disease, the recent study (6) demonstrating an absolute resistance of rheumatoid synovium to experimental RV infection suggested the possibility that a previously established virus infection might exist in rheumatoid synovium.…”
Section: S E Dmentioning
confidence: 99%
“…2f). Since a striking aspect of the cytopathic damage caused by MHV-3 in macrophages is an early increase in the permeability of the lysosomal membrane followed by massive lysosomal disruption (Allison & Mallucci, 1965;Mallucci, 1966), we examined the involvement of these organelles and found that in the presence of cytochalasin B, a considerable degree of lysosomal integrity had been retained both in single cells and in polykaryocytes.…”
Section: Discussionmentioning
confidence: 99%